Analysis of The Use of Air Defance Systrem Simulator in Supporting TAasks in Wingdik 700/Hanud - Juliar Adi Prasetya (Journal Research of Social Science, Economics, and Management, 2023)
Universal war is a conflict that involves many components of the state in defending the territory of the state. In order to face universal war, good preparation and training for soldiers is very important. Therefore, this study aims to evaluate the role of drills and simulations in preparing soldiers for universal warfare. This research uses a qualitative approach with a case study method in the Indonesian Air Force. The results showed that drills and simulations have an important role in preparing soldiers for universal warfare. Drills and simulations help improve soldiers' technical and tactical skills, improve situational awareness, and improve soldiers' ability to work in difficult and complex conditions. In addition, exercises and simulations also help identify weaknesses and strengths in the operation plan, so that necessary improvements can be made before the actual operation is carried out. However, the study also shows that exercises and simulations are not fully capable of mimicking the conditions of actual universal warfare. Therefore, exercises and simulations need to be made part of a broader training strategy, which includes training in more complex and realistic situations, as well as improvements in non-technical skills such as leadership, interpersonal skills, and ethics. The study concluded that training and simulation are one of the most important factors in preparing soldiers for universal warfare. Well-planned drills and simulations can help improve soldiers' ability to deal with difficult and complex situations in universal warfare, enabling them to act effectively in dangerous situations and defend national security.